Pregabalin in the reduction of pain and opioid consumption after burn injuries: A preliminary, randomized, double-blind, placebo-controlled study - Jones, Larry M.; Uribe, Alberto A.; Coffey, Rebecca; Puente, Erika G.; Abdel-Rasoul, Mahmoud; Murphy, Claire V.; Bergese, Sergio D. (Medicine (Baltimore), 2019)
The primary objective of the study was to evaluate the efficacy of 300 milligrams (mg) and 600 mg of pregabalin compared to placebo in the reduction of pain in patients with noncritical partial and full thickness burn injuries. A prospective, randomized, double-blinded, single center, placebo-controlled trial was conducted. Simple randomization method was used in this trial. After subjects met all the inclusion and none of the exclusion criteria, they were randomized and assigned to 1 of the 3 18-day treatments groups: Pregabalin 300 group, Pregabalin 600 group, or Placebo group. Demographics and clinical characteristics were recorded. The severity of pain was assessed by using the visual analog scale for pain intensity at baseline on day 3, day 9 ± 3, day 25 ± 7, day 90 ± 6, and day 180 ± 12. A total of 54 subjects were randomly assigned, and 51 were included in the data analysis. Demographics and clinical characteristics did not differ significantly between the 3 groups. There was a statistically significant difference in pain between the Pregabalin 300 and Pregabalin 600 groups (P-value = .0260). The Pregabalin 300 group had 17.93 units (95% confidence interval: 1.83-34.04) higher pain scores on average than the Pregabalin 600 group, regardless of time. The adjusted P-value comparing 0 to 300 was .1618, while the adjusted P-value for 0 versus 600 was .5304. There was an overall difference in pain across time regardless of study group (P-value = <.0001). An overall difference in opioid consumption (P-value = .0003) and BSHS (P-value = .0013) across time regardless of study group was noted. Pregabalin could be part of a promising multimodal analgesic regimen in noncritical burn population. Future placebo-controlled studies assessing the use of pregabalin in burn victim patients may further endorse our findings.